Antioxidant technology for durability enhancement in polymer electrolyte membranes for fuel cell applications - Kwon, Taehyun; Lim, Youngjoon; Cho, Jinwon; Lawler, Robin; Min, Byeong Jo; Goddard III, William A.; Jang, Seung Soon; Kim, Jin Young (Elsevier BV, 2022)
While polymer electrolyte membrane fuel cells (PEMFCs) have surged in popularity due to their low environmental impact and high efficiency, their susceptibility to degradation by in-situ generated peroxide and oxygen radical species has prevented their widespread adoption. To alleviate chemical attack on components of PEMFCs, particularly on polymer electrolyte membranes (PEMs), antioxidant approaches have been the subject of enormous interest as a key solution because they can directly scavenge and remove detrimental peroxide and oxygen radical species. However, a consequence is that long-term PEMFC device operation can cause undesirable adverse degradation of antioxidant additives provoked by the distinctive chemical/electrochemical environment of low pH, electric potential, water flux, and ion exchange/concentration gradient. Moreover, changes in the physical state such as migration, agglomeration, and dissolution of antioxidants by mechanical or chemical pressures are serious problems that gradually deteriorate antioxidant activity and capacity. This review presents current opportunities for and limitations to antioxidant therapy for durability enhancement in PEMs for electrochemical device applications. We also provide a summary of advanced synthetic design strategies and in-depth analyses of antioxidants regarding optimizing activity-stability factors. This review will bring new insight into the design to realization of ideal antioxidant nanostructures for PEMs and open up new opportunities for enhancing proliferation of durable PEMFCs.